1996
DOI: 10.1103/physrevb.53.116
|View full text |Cite
|
Sign up to set email alerts
|

Oholes associated with alkali acceptors inBaTiO3

Abstract: In BaTiO 3 the alkali ions Na and K, replacing Ba, lead to acceptor levels about 50 meV above the valence band edge. The structure of these defects can be studied by electron spin resonance, after light induced valence-band holes have been captured at neighboring O 2Ϫ ions. Hyperfine interaction with Na, Ba, and Sr impurities, adjacent to the paramagnetic O Ϫ , is identified. The holes are trapped stably below ϳ50 K. Their level position is determined by the temperature dependence of the relaxation rate of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 25 publications
4
36
0
Order By: Relevance
“…Refs. 35,36); the only exception known to us is an X α cluster calculation of F centers in LiNbO 3 . 37 Electron defects similar to what we have observed here are known, in particular, in partly covalent SiO 2 crystals (e.g., in the so-called E ′ 1 center an electron is also not localized inside V O but its wave function mainly overlaps with the sp 3 orbital centered on the neighboring Si atom 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Refs. 35,36); the only exception known to us is an X α cluster calculation of F centers in LiNbO 3 . 37 Electron defects similar to what we have observed here are known, in particular, in partly covalent SiO 2 crystals (e.g., in the so-called E ′ 1 center an electron is also not localized inside V O but its wave function mainly overlaps with the sp 3 orbital centered on the neighboring Si atom 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ESR study of KNbO 3 doped with Ti 4+ gives a proof that holes could indeed be trapped by such negatively charged defects [3]. For example, in BaTiO 3 , hole polarons were also found that are bound to Na and K alkali ions replacing Ba and thus forming a negatively charged site attracting a hole [4]. Primary candidates for such defects are cation vacancies.…”
Section: Introductionmentioning
confidence: 96%
“…replaces the Ba 2+ and had a negative charge relating to lattice. This negative charge stimulated strong hole-lattice interaction and result in hole localization [13].…”
Section: Resultsmentioning
confidence: 99%
“…The energy decrease determined by Jahn-Teller symmetric distortion may be not sufficient for self-trapping of a hole. Similarly to BaTiO 3 , where the presence of a negatively charged impurity ion stimulates self-trapping of a hole on the neighboring oxygen ion [13], the presence of a self-trapped electron in PWO will also stimulate self-trapping of a hole on the nearby ions. But, compared to ZnWO 4 , self-trapping of the hole will be delayed.…”
Section: +mentioning
confidence: 98%